2020
DOI: 10.1016/j.heliyon.2020.e03867
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' choices and factors affecting adoption of climate change adaptation strategies: evidence from northwestern Ethiopia

Abstract: Climate change is a major environmental and socioeconomic challenge in Ethiopia in recent decades. The study site is one of the climate change prone areas affected by climate variability and extreme events. Therefore, a better understanding of area-specific and adaptation is crucial to develop and implement proper adaptation strategies that can alleviate the adverse effects of climate change. Therefore, this work was aimed to identify determinants of farmers' adoption of climate change adaptation strategies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(102 citation statements)
references
References 21 publications
15
52
0
Order By: Relevance
“…This is consistent with Menberu and Yohannes ( 2014 ) who argued that large family is associated with higher labour endowment, which would enable a HH to accomplish various adaptation strategies. The present findings are in line with the findings of Marie et al ( 2020 ) who showed that a unit increase in the family member of a farmer resulted in 2%, 3.1% and 1.6% increase in the probability of farmers using improved crop varieties, soil conservation technique and mixed cropping, respectively, as adaptation strategy. This finding is also agreeable with finding of Gebrehiwot and Veen ( 2013 ) who revealed that farmers with large family size have higher probability of implementing adaptation measures than their counterparts.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with Menberu and Yohannes ( 2014 ) who argued that large family is associated with higher labour endowment, which would enable a HH to accomplish various adaptation strategies. The present findings are in line with the findings of Marie et al ( 2020 ) who showed that a unit increase in the family member of a farmer resulted in 2%, 3.1% and 1.6% increase in the probability of farmers using improved crop varieties, soil conservation technique and mixed cropping, respectively, as adaptation strategy. This finding is also agreeable with finding of Gebrehiwot and Veen ( 2013 ) who revealed that farmers with large family size have higher probability of implementing adaptation measures than their counterparts.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, they can easily adjust themselves to climate-related shocks. The findings are similar with the reports of Marie et al ( 2020 ) who indicated that a unit increase of a HH head significantly increases the probability of HH head using improved crop varieties and mixed cropping by 1.3% and 1.9%, respectively, in their study in north-western Ethiopia.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The binary logit model is more suitable in this case because the response on the dependent variable was either that a farmer had adopted or not adopted either traditional or scientific strategies. The binary logit model has been used in previous similar studies to investigate the relationship between a binary dependent variable and numerical explanatory variables [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…This is because agriculture is greatly dependent on climate change and variability ( Parry et al., 2007 ; Sarker and Rashid, 2012 ). Especially, smallholder farmers and poor communities in developing countries are more vulnerable to the impact of climate change ( Ancog et al., 2019 ; Frimpong et al., 2020 ; Kurukulasuriya and Rosenthal, 2013 ; Marie et al., 2020 ; Sarker and Rashid, 2012 ). As such, there is a high need for adaptation strategies ( Adzawla et al., 2019 ; Aniah et al., 2019 ; Idrissou et al., 2020 ; Muema et al., 2018 ), particularly ecosystem-based adaptation ( Maina et al., 2020 ) and/or area-specific adaptation measures ( Marie et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%